Randomized, sham-controlled, clinical trial of repetitive transcranial magnetic stimulation for patients with Alzheimer’s dementia in Japan - Saitoh, Youichi; Hosomi, Koichi; Mano, Tomoo; Takeya, Yasushi; Tagami, Shinji; Mori, Nobuhiko; Matsugi, Akiyoshi; Jono, Yasutomo; Harada, Hideaki; Yamada, Tomomi; Miyake, Akimitsu (Frontiers in Aging Neuroscience, 2022)
BACKGROUND: The several medications have been applied to Alzheimer’s dementia patients (AD) but their efficacies have been insufficient. The efficacy and safety of 4 weeks of repetitive transcranial magnetic stimulation (rTMS) in Japanese AD were evaluated in this exploratory clinical trial. METHODS: Forty-two patients, aged 60–93 years (average, 76.4 years), who were taking medication (>6 months) and had Mini-Mental State Examination (MMSE) scores ≤25 and Clinical Dementia Rating Scale scores (CDR-J) of 1 or 2, were enrolled in this single-center, prospective, randomized, three-arm study (i.e., 120% resting motor threshold [120%RMT], 90%RMT for the bilateral dorsolateral prefrontal cortex, and Sham). Alzheimer’s Disease Assessment Scale-Cognitive (ADAS-cog), Montreal Cognitive Assessment (MoCA-J), Clinical Global Impression of Change (CGIC), Neuropsychiatric inventory (NPI), and EuroQOL 5 Dimensions 5-Level (EQ-5D-5L) were administered. An active rTMS session involved applying 15 trains bilaterally (40 pulses/train at 10 Hz; intertrain interval, 26 s). Participants received ≥8 interventions within the first 2 weeks and at least one intervention weekly in the 3rd and 4th weeks. Intention-to-treat analysis included 40 patients (120%RMT [n=15], 90%RMT [n=13], and Sham [n=12]). RESULTS: In the full analysis set, MMSE, ADAS-cog, MoCA-J, CDR-J, CGIC, NPI, and EQ-5D-5L scores between the three groups were not significantly different. Two patients were erroneously switched between the 120%RMT and 90%RMT groups. Therefore, “as treated” patients were analyzed post-hoc, which revealed significant treatment efficacy in participants with MMSE scores ≥15, favoring the 120%RMT group over the Sham group. Responder analysis revealed 41.7% of the 120%RMT group had a ≥3-point improvement in the ADAS-cog versus 0% in the Sham group (Fisher’s exact test, p=0.045). The MoCA-J showed the same tendency but was not significant. Efficacy disappeared in week 20, based on the ADAS-cog and MoCA-J. No intervention-related serious adverse events occurred. CONCLUSION: This paper is the first report of using rTMS in Japanese AD patients. The treatment seems safe and promising for moderate-mild stage AD.